2012
DOI: 10.1111/j.1469-8986.2011.01353.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gestational age and postnatal age on speech sound processing in NICU infants

Abstract: The study examined the effect of gestational (GA) and postnatal (PNA) age on speech sound perception in infants. Auditory ERPs were recorded in response to speech sounds (CV syllables) in 50 infant NICU patients (born at 24–40 weeks gestation) prior to discharge. Efficiency of speech perception was quantified as absolute difference in mean amplitudes of ERPs in response to vowel (/a/–/u/) and consonant (/b/–/g/, /d/–/g/) contrasts within 150–250, 250–400, 400–700 ms after stimulus onset. Results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 110 publications
1
47
0
Order By: Relevance
“…However, in an event-related potential (ERP) study of discrimination of the Hindi /da/-/Da/ distinction, Peña and colleagues (2012) reported that infants born premature continued discriminating the Hindi (nonnative) consonants until they reached a chronological age that was approximately 12 weeks older than that of the full-term infants; that is, when they had reached the same gestational age (time from conception) as had the full-term infants. Similarly, a recent ERP study indicates that when listening to consonant-vowel syllables, the spontaneous neural response to speech in premature infants does not show obvious effects of listening experience in the first several months after birth (Key et al 2012). Thus, it appears that prior to a critical point in maturation-even when environmental input is provided-the developing human brain does not begin to settle on the native speech sound categories.…”
Section: Shifting Onset Timingmentioning
confidence: 94%
“…However, in an event-related potential (ERP) study of discrimination of the Hindi /da/-/Da/ distinction, Peña and colleagues (2012) reported that infants born premature continued discriminating the Hindi (nonnative) consonants until they reached a chronological age that was approximately 12 weeks older than that of the full-term infants; that is, when they had reached the same gestational age (time from conception) as had the full-term infants. Similarly, a recent ERP study indicates that when listening to consonant-vowel syllables, the spontaneous neural response to speech in premature infants does not show obvious effects of listening experience in the first several months after birth (Key et al 2012). Thus, it appears that prior to a critical point in maturation-even when environmental input is provided-the developing human brain does not begin to settle on the native speech sound categories.…”
Section: Shifting Onset Timingmentioning
confidence: 94%
“…14 Additionally, prior studies in infants showed that this window demonstrated the best variation between term and preterm infant’s response to sound. 21 …”
Section: Event-related Potential Methodologymentioning
confidence: 99%
“…However, infants born at or before 30 weeks of gestation could not reliably make those same distinctions compared to counterparts with the same postnatal age. Key et al (2012) suggest that a minimum level of brain maturity at birth is required for postnatal experience to impact perceptual narrowing and, in turn, milestones of language acquisition.…”
Section: The Black Box Of Prenatal Developmentmentioning
confidence: 99%
“…Key, Lambert, Aschner, and Maitre (2012) examined the effects of both gestational age and postnatal age of human infants in the NICU. When comparing infants born between 24-40 weeks gestation on auditory ERPs for native phoneme contrasts, Key et al (2012) found a threshold for prenatal development.…”
Section: The Black Box Of Prenatal Developmentmentioning
confidence: 99%
See 1 more Smart Citation